Strategi Komunikasi Digital dalam Program Corporate Social Responsibility PDAM Tirta Pakuan Bogor - Denariansyah, Azqia Aulia; Pranata, Rici Tri Harpin (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study examines the digital communication strategies implemented by PDAM Tirta Pakuan Kota Bogor in the implementation of its Corporate Social Responsibility (CSR) program. Using a descriptive qualitative approach and the Triple Bottom Line theory, which emphasizes balance between social, environmental, and economic aspects, this study analyzes how digital communication is used to disseminate information, increase public participation, and strengthen the company's image as a responsible public institution. The results show that PDAM utilizes various digital platforms such as websites, Instagram, Facebook, and YouTube social media, and implements interactive two-way communication to build collaboration with the community and other stakeholders. The CSR division plays a strategic role in managing the communication flow, which includes message planning, information dissemination, feedback reception, and evaluation of results in a transparent and accountable manner. This strategy supports social, environmental, and economic sustainability in accordance with the Triple Bottom Line theory, as well as increasing the effectiveness of PDAM Tirta Pakuan's CSR programs. Recommendations for future development include increasing social media interactivity, expanding collaboration, and strengthening digital evaluation to support the sustainability of CSR programs more effectively.